Amálgama odontológico : toxidade, armazenamento, manipulação e descarte - Oliveira, André Luiz de (2018)
Dental amalgam is a restorative material widely used in dentistry due to its physical and mechanical properties, it is a material of easy handling and low cost, but one of the negative aspects is the presence of mercury in its composition. Mercury is a metal toxic to living things and the environment, occupational exposure being one of the main sources of contamination by this metal. Among occupational activities at risk of exposure to mercury is dentistry. Studies show that the storage and disposal of amalgam waste can also contribute to the mercury contamination of dental offices, people working in them and the environment. During the making or removal of restorations the mercury can be released into the environment. Amalgam waste generated in dental practice is an important source of release of mercury into the environment if discarded in the common waste or discharged into the sewage system. This research will follow the typology described by Rudolf Carnap, insofar as he is concerned with real, observable and experimental facts and processes, typical of Factual Sciences. Sediment samples from the Sergipe river estuary were analyzed near the university hospital (HU) of the Federal University of Sergipe, in order to detect possible contamination and determination of mercury levels, and the characterization of the studied area. Following established standards, research will facilitate decision-making and the dissemination of information and knowledge such as policies from the perspective of the dimensions of sustainable development in economic, social, environmental, political and cultural aspects. Data were obtained on dental restorative materials and the environmental quality of the estuary of the Sergipe River. Information and research data will be made available to the general public and to the academic community, which may be used as a research source. It has been found that the estuary is contaminated with mercury at levels ranging from 0.107 to 0.240 mg / kg in periods of rain and drought, but the source of the polluting source can not be stated.